The Occupied Clinic : Militarism and Care in Kashmir - Varma, Saiba, 1983- (Book collections on Project MUSE., 2020)
"What does it mean to practice mental health care for a population besieged by 400 years of colonization and the ongoing violence of military occupation? Saiba Varma's ethnography of a psychiatric clinic in Kashmir considers how medical providers practice care in the context of curfews, strikes, and military violence, and hindered by inadequate access to essential drugs, equipment, and personnel. Yet, Varma also reveals how the work of the occupied clinic is inextricably linked to the persistence of the occupation. Instead of viewing the conflict in Kashmir as a war with Pakistan, the Indian Army has framed its operations in Kashmir as counterinsurgency-with the goal of restoring its image as a protective force for Kashmiri civilians. To achieve this aim, the Indian army engages in humanitarian projects like state and military mental health interventions. THE OCCUPIED CLINIC shows that under colonization and military occupation care is a political technology that can offer healing and comfort to those suffering, but can also produce inequality and inflict harm, extending colonial ideologies and practices. In Kashmir, over 60% of the civilian population have been diagnosed with depression, anxiety, dissociation, PTSD, or acute stress. Many Kashmiris experience what they call kamzori-a persistent fatigue, lack of strength, or loss of energy. Varma argues that kamzori is one manifestation of the way in which violence and colonization become embedded into the bodies of those living under occupation. She considers the Indian government's narrative that Kashmir is a "disturbed" area which can be returned to normal, showing instead that disturbance extends far beyond formal emergency rule and violence, seeping into everyday lives and public health infrastructures. When doctors suggest prescribing electroconvulsive therapy as a psychiatric treatment, patients understand this technology as inextricably linked to military torture methods-and indeed, in both cases, shock is being deployed as a quick solution to a structural problem. Finally, Varma turns to the Indian government's relief operations after the 2014 flood in Kashmir as an example of political humanitarianism-in which Kashmiris were encouraged to enact an attitude of gratitude and deference to the Indian government"--